Screening, Safety Evaluation, and Mechanism of Two Lactobacillus fermentum Strains in Reducing the Translocation of Staphylococcus aureus in the Caco-2 Monolayer Model - Peng, Zhen; Wei, Benliang; Huang, Tao; Liu, Zhanggen; Guan, Qianqian; Xie, Mingyong; Li, Haijuan; Xiong, Tao (Frontiers in Microbiology, 2020)
Staphylococcus aureus is a common commensal of humans and its translocation from gastro-intestine to peripheral organs and tissues could cause severe diseases and complications. This study focuses on the screening and characterization of Lactobacillus strains with significant inhibitory effect on the translocation of Staphylococcus aureus through Caco-2 monolayers. Firstly, strains with strong affinity for mucin and Caco-2 cells were obtained, via microtiter plate assay and adhesion assay, respectively. Obtained bacteria were further tested for their inhibitory effects on the growth of Staphylococcus aureus by well diffusion assay. Subsequently, two strains pre-incubated with Caco-2 monolayers were found to inhibit the translocation of Staphylococcus aureus CMCC26003 by 80.95% and 43.96%, respectively, via the transcellular translocation assay. These two strains were then identified to be Lactobacillus fermentum NCU3087 and Lactobacillus fermentum NCU3088. Secondly, the mechanism of inhibition was investigated by analyzing the relative concentration of tight junction proteins and proinflammatory cytokines of Caco-2 cells, by Western blot and ELISA assay, respectively. Results showed that both NCU3087 and NCU3088 significantly attenuated the degradation of occludin, claudin-1, ZO-1 and JAM-1 and suppressed the secretion of IL-6 and TNF-α induced by Staphylococcus aureus, to different extent. Moreover, two Lactobacillus strains could barely translocate the Caco-2 monolayers, had no hemolytic activity, displayed strong resistance to gastrointestinal fluids, and were sensitive or moderate sensitive to nine clinically relevant antibiotics. Collectively, this study identified two Lactobacillus strains with significant inhibitory effect on the translocation of Staphylococcus aureus and their safeness for application were evaluated, thereby providing potential solutions for prevention of Staphylococcus aureus and prophylaxis of related diseases.